Network Security Assessment : From Vulnerability to Patch. - Manzuik, Steve (Elsevier Science, 2006)
Solutions Fast Track; Frequently Asked Questions; Chapter 8. Vulnerability Management Tools; Introduction; The Perfect Tool in a Perfect World; Evaluating Vulnerability Management Tools; Commercial Vulnerability Management Tools; Open Source and Free Vulnerability Management Tools; Managed Vulnerability Services; Summary; Solutions Fast Track; Frequently Asked Questions; Chapter 9. Vulnerability and Configuration Management; Introduction; What is Vulnerability Management?; Patch Management; Building a Patch Test Lab; Patch Distribution and Deployment; Configuration Management; Summary.